The other side of love : handling anger in a godly way - Chapman, Gary D., 1938- (Chicago, Ill. : Moody Press, 1952)
Filled with insights and techniques that have helped hundreds of individuals and families to find a better way to deal with anger, The Other Side of Love will help you to understand the source of your anger- and guide it toward productive purposes.
Introduction : understanding and processing anger -- Why do people get angry? -- What is the purpose of anger? -- How can I make anger productive? -- When anger is distorted -- Processing distorted anger -- Destructive responses to anger -- Processing long-term anger -- Anger and forgiveness -- Anger in marriage -- Teaching children to handle anger -- When you are angry with God -- When you are angry at yourself -- When you encounter an angry person -- Epilogue : God's nature in us.
Includes bibliographical references.
Keywords: Anger -- Religious aspects -- Christianity